Estudo espectroscópico do íon Eu3+ incorporado na matriz inorgânica de aluminato de gadolínio obtido por meio do processo sol gel não hidrolítico - Matos, Marcela Guedes (2012)
The emission of light energy by lanthanide ions activated in mixed oxides has been applied in various technological fields such as phosphors for flat, wide, and high definition displays and has been used in various luminescent devices like PDP – plasma display panel, and LED - light emitting diodes, as well as in cathode ray tube televisions, solid state laser, lamps, and signaling paints. Luminescent materials have been prepared by solid state reactions at high temperatures (~1400 °C). The perovskite gadolinium aluminate has been synthesized by other wet-chemical techniques, such as Pechini (900 °C), different sol-gel routes (950 – 1200 °C), combustion (1000 – 1200 °C), and solvothermal methods (1000 – 1400 °C). The gadolinium oxide has been produced by these routes; however, it has also been prepared by the combustion (600 °C) and Pechini (900 °C) methods. The latter methods have been widely exploited due to the use of lower heating conditions for the achievement of the final product. Nevertheless, expensive and sophisticated equipment is necessary. The present study has been conducted so as to show that the non-hydrolytic solgel route can be efficient in the production of these materials, which have not yet been prepared by this process. To this end, four different gadolinium oxide matrices containing different concentrations of the activator Eu3+, namely 0.1, 1.0, 3.0, and 5.0 %, have been synthesized herein, using metal chlorides as precursor. The X-ray diffraction patterns revealed that the materials treated at 600 °C presented initial crystallization of gadolinium oxychloride, whereas the heat-treatment favored initial crystallization of gadolinium oxide. Samples treated at 1000 °C were significantly crystalline, and there was formation of gadolinium aluminate under 1.0 % Eu3+ ion. As for the other Eu3+ concentrations, the predominant formation of gadolinium aluminate was detected. The excitation spectra of the activator Eu3+ displayed broad bands relative to the charge transfer from the oxygen ion ligand to the Eu3+ ions, as well as bands corresponding to the levels of the excited state of the Gd3+ and Eu3+ ions. The emission spectra of the activator were monitored in the charge transfer band and in the excited state levels of the trivalent Eu3+ ion – 5L6 and 5D2. There was evidence of strong emission in the region of 614 nm, characteristic of the 5D0 →7F2 transition (the red spectral region). The high values of lifetime and emission quantum yield led to the conclusion that the non-hydrolytic sol gel route is an efficient method for the preparation of luminescent materials and can be employed in various technologies critical to the present day, such as electronic devices, laser, and lamps, among others.